Technological Capabilities of Chinese Enterprises: Who is Going to Compete Abroad? - Philipp Böing; Elisabeth Müller (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2012)
The objective of this study is to investigate the relation between increasing Chinese high-tech exports and the technological capabilities of Chinese companies. China s recent innovation policy provides substantial incentives for companies to pursue technological upgrading and internationalization strategies. For our analysis, we extend models of New New Trade Theory to include the aspect of the technological capabilities of companies. We use the share of international patent applications as a proxy for exports and find that companies with higher total factor productivity and more valuable technology, as measured with citations received, are more likely to go international. Considering the implications of transport cost, we find that companies located in China s coastal region are more likely to export. We do not find evidence that the inclination to export is dominated by policy considerations.
Keywords: F23; O34; O31; 330